Enhanced photocatalytic characteristics and low selectivity of a novel Z-scheme TiO2/g-C3N4/Bi2WO6 heterojunction under visible light. (January 2021) - Fang, Guoli; Li, Mengyue; Shen, Hongfang; Yang, Shaolin; Israr, Jahanzaib
Abstract: A new Z-scheme T i O 2 / g - C 3 N 4 / B i 2 W O 6 ternary heterojunction has been successfully synthesized through a simple hydrothermal method. As-fabricated ternary heterojunction could exhibit enhanced photocatalytic activities in Rh B, MB and phenol using visible light irradiation than those from T i O 2, g - C 3 N 4, B i 2 W O 6 nanostructures and g - C 3 N 4 / B i 2 W O 6 heterojunction. These improved photocatalytic activities were mainly because of the decrease on the recombination of photo excited hole-electron pairs, thus enhancing the lifetime of photo induced charge carrier in a Z-scheme heterojunction. Furthermore, the combined action of ·OH, ·O2, h + and e − active species effectively promoted the photocatalytic process, which made the ternary heterojunction having low selectivity to the photo-degradation of different organic pollutants. After the fifth cyclic utilization of the ternary heterojunction, the degradation rate of Rh B, MB and phenol could be still reached to 91%, 78% and 63%, respectively. This illustrates that the obtained heterojunction has enhanced visible light photocatalytic efficacy including low selectivity and high activity with excellent stability for practical purposes. Graphical abstract: Image 1